Free water as a potential mediator linking basal ganglia peri-vascular spaces to white matter hyperintensities in cerebral small vessel disease - Feng, Weishun; Lei, Xinjun; Wang, Xinbin; Xu, Shida; Xu, Zhihua (Frontiers in Neuroscience, 2025)
ObjectiveWhite matter hyperintensities (WMH) are common in cerebral small vessel disease (CSVD) and have been linked to an increased risk of stroke and cognitive impairment. Emerging evidence suggests that perivascular spaces (PVS) and impaired interstitial fluid (ISF) drainage may contribute to WMH development. This study aimed to investigate the topographical association between PVS and WMH severity, and to explore whether ISF content, measured as diffusion tensor imaging (DTI)-derived free water (FW), mediates this relationship.MethodsWe enrolled 125 patients with CSVD who underwent multimodal brain MRI. PVS burden was visually rated in the basal ganglia (BG PVS) and centrum semiovale (CS PVS). WMH volumes were segmented and normalized to intracranial volume. FW maps were generated from DTI using bi-tensor modeling.ResultsPatients with high grade BG PVS exhibited significantly greater normalized WMH volumes compared to those without (p < 0.05), whereas no significant difference was found for CS PVS. Multivariable analysis indicated that high grade BG PVS was independently associated with increased WMH burden (β = 0.217, 95% CI: 0.041–0.393; p < 0.05). Mediation analysis demonstrated that FW mediated the association between high grade BG PVS and WMH severity (β = 0.082, 95% CI: 0.012–0.207; p < 0.05) adjusting with age and vascular risk factors.ConclusionOur findings suggest a topographical specificity in the PVS-WMH relationship, with basal ganglia PVS playing a more critical role. Moreover, elevated ISF, as indicated by DTI-based FW, may be an important intermediary linking PVS enlargement to WMH burden, providing new insights into the pathophysiology of CSVD.